FAKTOR - FAKTOR YANG MEMPENGARUHI BELANJA DAERAH PADA KABUPATEN/KOTA JAWA TIMUR - Liando, Ivoni Ike; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to test the influence of local own source revenue (PAD), general allocation fund (DAU), special allocation fund (DAK), and profit sharing fund (DBH), Flypaper Effect (FEF) and the numbers of the population(JPE) to the local expenditure (BED). Sample consisted of 29 districts and 9 in East Java with 148 observation reports Actual Budget and Expenditure 2012-2015 year, with resources BPK and BPS. Thisexamination has been carried out by using multiple linear regressions analysis technique and the instrument of SPPS application (Statistical Product and Service Solutions). The result of the research which has been done by using multiple linear regressions shows that local own source revenue (PAD), general allocation fund (DAU), special allocation fund (DAK), and proift sharing fund (DBH), Flypaper Effect (FEF) and the numbers of the population (JPE) to the local expenditure (BED). Meanwhile, the flypaper effect does not give any influence to the local expenditure, with the R-Squared 0.988 or 98.8%, it shows that the variables in the modelsare able to predict the local expenditure, meanwhile 1.2% is influenced by other variableswhich are included in the model.Keywords: Local own source revenue (PAD), Equalization fund, Flypaper Effect (FEF), The numbers of the population (JPE), Local expenditure (BED)